Sifat Optik Lapisan Tipis In2O3 yang Ditumbuhkan dengan Metode MOCVD - Horasdia Saragih; Hasniah Aliah; Euis Sustini; Albert Manggading Hutapea (Institut Teknologi Bandung, 2010)
The In2O3 thin films have been deposited on glass substrate by MOCVD method using In(TMHD)3 metal organic precursor. The growth parameters, such as bubbler temperature 200oC, bubbler pressure 260 Torr, substrate temperature 300oC, flow rate of Ar gas 50 sccm, flow rate of O2 gas 50 sccm, chamber pressure 2x10-3 Torr, and duration of growth from 120 to 180 minutes were used. Three In2O3 thin films with different thicknesses, i.e. 531, 434, and 404 nm were resulted. Optical transmissions of the thin films in the visible wavelength were above of 80%, and not significantly influenced by thickness difference up to about of 127 nm. The optical band gap and Urbach energy band of thin films were 3,76-3,80 eV and 0,20-0,22, respectively. The thin films deposited have indirect forbidden transition.